Pengaruh Harga Tiket Online dan Pelayanan Terhadap Keputusan Pembelian Tiket Maskapai Garuda Indonesia Pada Mahasiswa di Yogyakarta - Anggia Caroline Br Simanjuntak; Yunus Purnama (Jurnal Publikasi Ilmu Manajemen, 2025)
The advancement of information technology and the internet has enabled the emergence of various online ticket booking platforms, providing users with a convenient and efficient way to purchase flight tickets. This research aims to analyze and determine the extent of the influence of online ticket prices and service quality on the ticket purchasing decisions for Garuda Indonesia. This study employs a quantitative method with data collection techniques obtained directly through observation, documentation, and questionnaire distribution, targeting 200 undergraduate students in the Yogyakarta province from December 2023 to January 2024. The t-test results indicate that the ticket price variable (HT) has a significant impact on the ticket purchasing decision (KPM) for Garuda Indonesia among students in Yogyakarta, as evidenced by a t-value of 2.026 with a significance value (Sig.) of 0.044. The partial test results also show that service quality (KPY) has a very significant impact on the ticket purchasing decision (KPM) for Garuda Indonesia among students in Yogyakarta, with a t-value of 6.448 and a significance value (Sig.) of 0.000. The findings reveal that both ticket price and service quality significantly influence the ticket purchasing decisions for Garuda Indonesia, with service quality having a greater impact.